Facilitating lifestyle changes to manage menopausal symptoms in women with breast cancer. Issue 9 (September 2015) - Anderson, Debra J.; Seib, Charrlotte; McCarthy, Alexandra L.; Yates, Patsy; Porter-Steele, Janine; McGuire, Amanda; Young, Leonie
Abstract Objective: Women diagnosed as having breast cancer may experience difficulties with posttreatment effects such as menopausal symptoms. The aims of this pilot study were to (1) evaluate the impact of a multimodal lifestyle program on reducing menopausal symptoms in women with breast cancer and (2) examine the impact of the program on health-related quality of life (HRQoL) and adherence to lifestyle recommendations. Methods: Overall, 55 women aged 45 to 60 years with one moderate to severe menopausal symptom and a history of breast cancer were randomized into an intervention group (n = 26) or a control group (n = 29). Women in the intervention group received a lifestyle intervention (The Pink Women's Wellness Program) that included clinical consultations and a tailored health education program. Measurements of menopausal symptoms (Greene Climacteric Scale), HRQoL (SF-12 and Functional Assessment of Cancer Therapy—Breast), and modifiable lifestyle factors (food intake, physical activity, smoking and alcohol use, and sleep disturbance) were taken at baseline and 12 weeks. Results: Women in the intervention group reported clinically significant reductions in many menopausal symptoms, specifically somatic symptoms (d = 0.52), vasomotor symptoms (d = 0.55), sexual dysfunction (d = 0.65), and overall menopausal symptoms (d = 0.54), at 12 weeks compared with the control group (d = 0.03, d = 0.24, d = 0.18, and d = 0.05, respectively). Women in the intervention group reported improvements in Functional Assessment of Cancer Therapy—Breast subscale scores, physical well-being and functional well-being, and Functional Assessment of Cancer Therapy—General total scores (intervention group: d = 0.54, d = 0.50, and d = 0.48, respectively; control group: d = 0.22, d = 0.11, and d = 0.05, respectively). Conclusions: The Pink Women's Wellness Program is effective in decreasing menopausal symptoms, thus improving HRQoL. This being a pilot study, further research is recommended to investigate the benefits of combining nonpharmacological interventions for women with breast cancer to reduce their treatment-related menopausal symptoms.